Prevalence of preterm birth and associated maternal factors at Teaching Hospital Anuradhapura, Sri Lanka - Dharmadasa, U.K.; Premathilake, S.M.S.P.; Kamalarupan, L.; Sasrubi, S. (Sri Lanka Journal of Child Health,, 2025)
Background: Preterm birth is a primary cause of newborn morbidity and mortality. Preterm birth rate in Sri Lanka ranges from 10-15 per 1000 live births. Objectives: To assess the prevalence and maternal factors associated with preterm birth at Teaching Hospital Anuradhapura, Sri Lanka Method: A hospital-based descriptive cross-sectional study was conducted among all mothers attending postnatal wards, Obstetrics and Gynaecology Unit during October 2023 at Teaching Hospital Anuradhapura. Details of pregnancy, obstetrics and birth profile were collected using an interviewer-administered questionnaire and data extraction sheet. Results: Data were collected from all mothers (n=597) during their postnatal hospital stay. Prevalence of preterm birth was 9.5%. Mode of delivery, pregnancy outcome (singleton/twin), previous history of preterm labour, previous history of gestational diabetes mellitus, consanguinity, stressful events during pregnancy, pregnancy complications like premature rupture of membranes, pregnancy induced hypertension, placental abruption, oligohydramnios, cervical incompetence, chorioamnionitis and vaginal candidiasis were significantly associated with preterm birth. Conclusions: Prevalence of preterm birth was 9.5% in Anuradhapura Teaching Hospital. Mode of delivery, pregnancy outcome, previous history of preterm labour, previous history of gestational diabetes mellitus, consanguinity, stressful events during pregnancy, pregnancy complications and vaginal candidiasis were significantly associated with preterm birth.
Keywords: Preterm birth; Anuradhapura Teaching Hospital; Pregnancy complications; Maternal health